The World Wide Web Conference 2019
DOI: 10.1145/3308558.3313747
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Temporal Convolutional Networks for Dynamic Recommender Systems

Abstract: Recommender systems that can learn from cross-session data to dynamically predict the next item a user will choose are crucial for online platforms. However, existing approaches often use out-ofthe-box sequence models which are limited by speed and memory consumption, are often infeasible for production environments, and usually do not incorporate cross-session information, which is crucial for effective recommendations. Here we propose Hierarchical Temporal Convolutional Networks (HierTCN), a hierarchical dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 24 publications
0
60
0
Order By: Relevance
“…Other methods based on Convolutional Neural Networks (CNN) [40], Memory Network [5] and Attention Models [22] have also been explored. The hierarchical structure generalized from RNN, Attention or CNN based models [7,31,45] is used to model transitions inter-and intra-sessions. The recent work [45] by You et al showed that using Temporal Convolutional Network to encode and decode session-level information and GRU for user-level transition is the most effective hierarchical structure.…”
Section: Sequential Recommendationmentioning
confidence: 99%
See 4 more Smart Citations
“…Other methods based on Convolutional Neural Networks (CNN) [40], Memory Network [5] and Attention Models [22] have also been explored. The hierarchical structure generalized from RNN, Attention or CNN based models [7,31,45] is used to model transitions inter-and intra-sessions. The recent work [45] by You et al showed that using Temporal Convolutional Network to encode and decode session-level information and GRU for user-level transition is the most effective hierarchical structure.…”
Section: Sequential Recommendationmentioning
confidence: 99%
“…The hierarchical structure generalized from RNN, Attention or CNN based models [7,31,45] is used to model transitions inter-and intra-sessions. The recent work [45] by You et al showed that using Temporal Convolutional Network to encode and decode session-level information and GRU for user-level transition is the most effective hierarchical structure. Nevertheless, as many studies borrow sequence models from natural language modeling task directly, their model performance is usually limited by the relatively small size and sparse pattern of user behaviors, compared to the nature language datasets.…”
Section: Sequential Recommendationmentioning
confidence: 99%
See 3 more Smart Citations